DEVELOPMENT OF SUSHI JALI - JALI WITH SUBTITUTIONS RAW MATERIALS JALI-JALI SEEDS (Coix Lacryma-Jobi) - Andian Ari Anggraeni, Retno Wulandari, (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to develop a sushi product recipes with the substitution jali seeds seed, to determine the value of the product received from the public by hedonic test and to determine the content of the nutritional value of the product substitution sushi with jali seeds seeds. This type of research is the R & D or research and development with the aim to find and develop products. Development model is carried by 4D (Define, Design, Development, and Dissemination). In this development model testing at each stage. Tests carried out by two people trained panelists, 30 panelists semi-trained and 60 untrained panelists. Results showed recipes 3 with substitution of jali seeds 100% get highest rates compared to recipe 1 and 2. Received power product development sushi jali seeds are in like and very like assessment. The assessment is done by untrained panelists of 60 people with an average score of between 3.4 up to 3.6 for all the assessment indicators. Based on the calculation of nutritional adequacy rate sushi jali seeds 100 grams is 1% fat, 5% protein and 7% carbohydrate. Keywords: sushi, jali seeds, R & D